The First Year Gender Pay Gap Reporting in Ireland: A Sociological Analysis - O'Sullivan, Sara (The Economic and Social Review, 2024)
In 2022 organisations in the Republic of Ireland with 250+ employees were required to report on their hourly gender pay gap for the first time. This research combines a comparative quantitative analysis of the statistical data included in 578 published reports and a thematic analysis of the accompanying narratives. The majority of organisations reported a higher mean and median rate of pay for male employees. The overall average GPG across all employees was 11.82 per cent, with a smaller median gap of 8.37 per cent. The reports allow us to see how organisational level characteristics impact the gender pay gap. The variations across organisations, industries and sectors challenge common sense framings of the gender pay gap as a natural and inevitable feature of the contemporary workforce. While the introduction of mandatory GPG reporting marked an important step towards pay transparency, both the implementation and the content of the reports point to significant weaknesses that could undermine the potential to foster genuine change.